"Medea dos fuxidos" by Manuel Lourenzo and "Medea" by Euripides. Textual Influences and Ethical-emocional Concepts - Cendán Teijeiro, Noelia (Madrygal. Revista de Estudios Gallegos, 2015)
Medea dos fuxidos, a scenic poem by Manuel Lourenzo, dramatizes most of the subject matter contained in the Greek tragedy Medea. Although the Galician playwright makes an excellent cultural adaptation by reformulating all types of aspects (secondary characters, setting, anthropological ideas...), the work retains, as this study shows, important features of the Greek version, namely textual thematic line, concomitants and dramatic characterization.
Keywords: Medea; Eurípides; Medea dos fuxidos; Manuel Lourenzo